Faktor – Faktor yang Mempengaruhi Pemasaran Kopi Arabika (Study Kasus di Koperasi Klasik Beans Kabupaten Bandung Jawa Barat) - Teuku Ivan Hadriyana; Tuhpawana Priatna Sendjaya; Aik Tachri (Fakultas Pertanian Universitas Winaya Mukti, 2023)
The purpose of this study is to identify the factors that influence the price of Arabica coffee in the Klasik Beans Cooperative, analyze the factors that influence the marketing of Arabica coffee in the Klasik Beans Cooperative, formulate the dominant factors that influence the relevant marketing used by the Klasik Beans Cooperative. Based on the results of regression analysis and further testing, the variables that affect the price of coffee are the amount of production, coffee quality and production risk. While the variables of land area and labor have no effect. Based on the results of regression analysis and further testing, the variables that affect income are the amount of production, coffee quality, land area and labor. While the production risk variable has no effect.